Subjective cognitive decline and stage 2 of Alzheimer disease in patients from memory centers. Issue 2 (22nd April 2022) - Jessen, Frank; Wolfsgruber, Steffen; Kleineindam, Luca; Spottke, Annika; Altenstein, Slawek; Bartels, Claudia; Berger, Moritz; Brosseron, Frederic; Daamen, Marcel; Dichgans, Martin; Dobisch, Laura; Ewers, Michael; et al.
Abstract: Introduction: It is uncertain whether subjective cognitive decline (SCD) in individuals who seek medical help serves the identification of the initial symptomatic stage 2 of the Alzheimer's disease (AD) continuum. Methods: Cross‐sectional and longitudinal data from the multicenter, memory clinic–based DELCODE study. Results: The SCD group showed slightly worse cognition as well as more subtle functional and behavioral symptoms than the control group (CO). SCD–A+ cases (39.3% of all SCD) showed greater hippocampal atrophy, lower cognitive and functional performance, and more behavioral symptoms than CO–A+. Amyloid concentration in the CSF had a greater effect on longitudinal cognitive decline in SCD than in the CO group. Discussion: Our data suggests that SCD serves the identification of stage 2 of the AD continuum and that stage 2, operationalized as SCD‐A+, is associated with subtle, but extended impact of AD pathology in terms of neurodegeneration, symptoms and clinical progression.